2022
DOI: 10.3201/eid2803.211435
|View full text |Cite
|
Sign up to set email alerts
|

Rising Incidence of Legionnaires’ Disease and Associated Epidemiologic Patterns, United States, 1992–2018

Abstract: Rising incidence was associated with increasing racial disparities, geographic focus, and seasonality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…The analysis does not include any data from the Southeastern US because these states either do not contribute to the HCUP dataset or do not provide monthly data; this is a major limitation, as states in this region are most prone to cyclonic storms. However, regions with the highest incidence of Legionnaires’ disease were included in the analysis, and states that did not contribute to the HCUP dataset generally had lower incidence compared to the national average [ 71 ]. A recent analysis of Legionnaires’ disease epidemiological trends in the United States between 1992 and 2018 found that age-standardized average incidence was higher in the Northeast and Midwest compared to the South and West, and highest in New England and the Mid-Atlantic states [ 71 ]; these geographic differences in incidence were more pronounced later in the time series (after 2002), which overlaps with most of the study period in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis does not include any data from the Southeastern US because these states either do not contribute to the HCUP dataset or do not provide monthly data; this is a major limitation, as states in this region are most prone to cyclonic storms. However, regions with the highest incidence of Legionnaires’ disease were included in the analysis, and states that did not contribute to the HCUP dataset generally had lower incidence compared to the national average [ 71 ]. A recent analysis of Legionnaires’ disease epidemiological trends in the United States between 1992 and 2018 found that age-standardized average incidence was higher in the Northeast and Midwest compared to the South and West, and highest in New England and the Mid-Atlantic states [ 71 ]; these geographic differences in incidence were more pronounced later in the time series (after 2002), which overlaps with most of the study period in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, regions with the highest incidence of Legionnaires’ disease were included in the analysis, and states that did not contribute to the HCUP dataset generally had lower incidence compared to the national average [ 71 ]. A recent analysis of Legionnaires’ disease epidemiological trends in the United States between 1992 and 2018 found that age-standardized average incidence was higher in the Northeast and Midwest compared to the South and West, and highest in New England and the Mid-Atlantic states [ 71 ]; these geographic differences in incidence were more pronounced later in the time series (after 2002), which overlaps with most of the study period in this analysis. Future studies should examine the associations among hydrometeorological conditions and Legionnaires’ disease throughout the US, particularly in the Southeast, but the regions included in the study capture the states with the highest Legionnaires’ disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Legionella spp. have been shown to be increasing in incidence ( Barskey et al., 2022 ). Recent findings from our group have shown that the distribution of legionella serogroups varies greatly between geographic regions and the prevalence of other serogroups may be underestimated due to the widespread clinical use of urinary antigen tests in diagnosis, which selectively targets Legionella pneumophila serogroup 1 ( Head et al., 2019 ).…”
Section: Effects Of Existing and Potential Immunomodulators On Pneumo...mentioning
confidence: 99%
“…had shown that non- pneumophila serogroup 1 Legionella (including L. bozemanae , L. micdadei , L. anisa , and other strains of L. pneumophila ) were found to increase mortality while also doubling the likelihood of requiring intensive care unit (ICU) care in individuals coinfected with HIV and M. tuberculosis or HIV and P. jirovecii ( Head et al., 2019 ). As reported by the CDC, cases of Legionella in the US have been increasing significantly over the past 20 years ( Barskey et al., 2022 ). A similar trend had also been noted in France by Campese et al., following the establishment of mandatory reporting of Legionella and stricter detection protocols ( Campese et al., 2011 ).…”
Section: Effects Of Existing and Potential Immunomodulators On Pneumo...mentioning
confidence: 99%
“…The reason for this widespread increase is unclear. Apart from improved disease surveillance, the design and maintenance of building infrastructure, and an ageing and increasingly susceptible population, Barskey et al suggest that the geographical distribution and increasing seasonal frequency of cases in summer indicate weather patterns may play a role in the increasing LD incidence 7 . Studies from the European Centre for Disease Prevention and Control (ECDC) and others also consider climate change as one of the potential drivers of the increasing temporal trend 6,8 .…”
Section: Introductionmentioning
confidence: 99%